Peningkatan Hasil Belajar Siswa Dengan Model Pembelajaran Project Based Learning (PJBL) Kombinasi Metode Two Stay Two Stray (TSTS) Pada Mata Pelajaran Kejuruan Desain Komunikasi Visual (DKV) - Escalunna Portalindo; Efrizon; Dedy Irfan; Hadi Kurnia Saputra (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research is a Classroom Action Research (CAR) which aims to improve student learning outcomes through the application of the Project Based Learning (PjBL) learning model combined with the Two Stay Two Stray (TSTS) strategy in the vocational subject of Visual Communication Design (DKV). The population in this study was class XI DKV SMK Negeri 2 Padang Panjang in the 2024/2025 academic year, totaling 76 people. Based on the results of the study, it can be concluded that: (1) there is an increase in student learning outcomes with the Project Based Learning (PjBL) learning model combined with the Two Stay Two Stray (TSTS) method in the vocational subject of visual communication design (DKV). Based on the normality test analysis, the first posttest was 0.676 and the second posttest was 0.573. Then the average comparison test at the final stage using the t-test obtained tcount = 20.39 and ttable = 2.06 at a significance level of α = 5%, tcount > ttable as a result H0 was rejected. So it can be concluded that there is an increase in student learning outcomes with the Project Based Learning (PjBl) learning model combined with the Two Stay Two Stray (TSTS) method in the vocational subject of visual communication design (DKV). And (2) There is an increase in learning outcomes using the Project Based Learning (PjBl) learning model combined with the Two Stay Two Stray (TSTS) method. With an average score on the first posttest of 71.21 and on the second posttest of 78.54. This shows that there is a comparison of student learning outcomes using the Project Based Learning (PjBl) learning model combined with the Two Stay Two Stray (TSTS) method.